Complex network analysis of the Brazilian power grid - Martins, Gabriela da Cruz; Ribeiro, Fabiano; Oliveira, Leonardo Santos; Forgerini, Fabricio Luchesi (Scientia Plena, 2018)
In the last decades, power grids and other energy transmission networks have received attention from the network literature. In this work, we studied one of the most important static features of power grids, their topology, with focus on the Brazilian Power Grid (BPG). We obtained the spatial structure of the BPG from the ONS (Electric System National Operator), consisting of its high-voltage transmission lines, electric stations and substations. Some traits had to be ignored, such as the local low-voltage substations and as well the dynamic features of the network. We analyzed the complex network of the BPG and its statistics, such as the mean degree, the degree distribution, the network size and the clustering coefficient to characterize the complex network. We also detected critical locations in the network and, therefore, points that are more susceptible to cascading failures and even to blackouts. Our results show that the BPG is functional against random failures, regarding random removal of links and connections, in terms of the size of the largest cluster. We observe that when a fraction ρ of the links are randomly removed, the network may break down into smaller, disconnected parts. However, the largest component of the power grid remains connected. We believe that even a static study of the network topology can help to identify the critical situations and also prevent failures and possible blackouts.